Ministry in laïque France: Understanding history to confront present challenges - Davis, Stephen M. (Missiology, 2021)
This article attempts to provide insight into the challenging and changing religious context for cross-cultural ministry in France in the 21st century. Many of these challenges exist due to the religious history of France, the marginalization of religion, and the unwelcome presence of foreign missionaries in secular France. French laïcité presents a specificity in origin, definition, and evolution which arises from a unique historical context leading to the Law of Separation of Churches and state in 1905. The law abrogated the 1801 Napoleonic Concordat with the Vatican, disestablished the Roman Catholic Church, ended centuries of religious turmoil, declared state neutrality in religious matters, and continues as a subject of debate and dissension 100 years later with the emergence of Islam as the second largest religion in France. Cross-cultural workers enter a ministry context where religion has been progressively removed from public space.